Selected Practices of Delegation and it’s Influence on Principals’ Management of Public Secondary Schools in Rachuonyo South Sub-County Kenya - Ochieng, Muma Hillary; Odhiambo , Rhoda A.; John , Yambo M. (International Journal For Research In Educational Studies, 2019)
The study assessed selected elements of delegation of duty and their influence on principals’ effective management of public secondary schools in Rachuonyo south Sub-County, Kenya. It was investigated under the following objectives; to determine the influence of communication on effective management of secondary schools; to find out the contribution of motivation on effective management; to establish the effect of expertise consideration on effective management and to establish the importance of job description on effective management of secondary schools. The study employed descriptive survey design. The study population consisted of 75 principals, 75 Deputy Principals, 350 Heads of department and 434 teachers. Saturated sampling technique was used to sample 75 Deputy Principals. Simple random sampling technique was used to sample 25 Principals which is 33.3% of the population, 150 Heads of Departments which is 42.8% of the population and 150 Teachers which is 34.5% of the population. Data was collected using questionnaires and interviews. Five schools from the neighboring Rachuonyo North Sub-County were used in pilot study to ensure reliability of the instruments. Face and content validity of the instruments was determined by experts who were my supervisors and the impressions on the instruments improved based on their advice before using them for data collection. Quantitative primary data was analyzed using descriptive statistics that is, frequencies and percentages. Qualitative primary data were transcribed and organised into themes and categories as they emerged. The study found out that principals communicate with the staff through use of organized staff meetings which had a percentage rate of 36.6, 29.4 and 32.4. Motivation of the staff was found to be done once in a while by the principals which had a percentage rate of 50.4, 43.7 and 45.3. Expertise consideration during delegation of duty was found to result into improved school mean which had a percentage rate of 30.5, 31.0 and 17.8. Job description was found to improve on quality work output which had a percentage rate of 35.1, 30.1 and 45.3. The study recommends that the Government through Teachers Service Commission provide delegation skills trainings for secondary school principals so as to foster productive delegation of duty that is beneficial for teacher career development and student performance. The government should address teacher motivation by making provision for more funding to schools to enable teacher motivation possible to boost teacher morale. Secondary school principals’ should learn to delegate duties to skilled personnel and avoid allocating duties to loyal staff to enable the attainment of goals and objectives of education. Finally this paper recommends that principals should learn the art of delegation to ensure that the duty delegated is well described and the objectives to be met well stated. From the findings of the study, it is suggested that more comprehensive studies be undertaken to investigate other factors affecting delegation of duty other than communication, motivation, expertise consideration and job description. Ethical consideration was put in place to ensure the respondents remained anonymous throughout the study.